1984
DOI: 10.1128/aac.26.4.476
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antiviral effects of ribavirin and the C-nucleoside analogs tiazofurin and selenazofurin against togaviruses, bunyaviruses, and arenaviruses

Abstract: Binary combinations of the N-nucleoside ribavirin (1-3-D-ribofuranosyl-1,2,4-triazole-3-carboxamide) and the C-nucleoside analog selenazofurin (2-f8-D-ribofuranosylselenazole-4-carboxamide) or tiazofurin (2-(0-Dribofuranosylthiazole-4-carboxamide) were tested in vitro for activity against Venezuelan equine encephalomyelitis, Japanese encephalitis, yellow fever, Rift Valley fever, Korean hemorrhagic fever, and Pichinde viruses. The 50% effective dose for each compound alone or in a series of combinations was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(50 citation statements)
references
References 19 publications
2
47
1
Order By: Relevance
“…Selenazofurin was previously shown to have antiviral activity against a number of different viruses in vitro (5,8,9). We demonstrated that selenazofurin also inhibits replication of influenza A and B viruses in vitro (ID50 = 25 and 19 ,uM, respectively).…”
Section: Discussionmentioning
confidence: 75%
“…Selenazofurin was previously shown to have antiviral activity against a number of different viruses in vitro (5,8,9). We demonstrated that selenazofurin also inhibits replication of influenza A and B viruses in vitro (ID50 = 25 and 19 ,uM, respectively).…”
Section: Discussionmentioning
confidence: 75%
“…We determined that RBV had a narrow TI of 4.7 Ϯ 2.5 in the BVDV assay, with only a slight margin between the concentration required for antiviral effects and that causing cytotoxicity. RBV was (20) and 28 g/ml (29) also determined with inhibition-of-CPE assays, yet it was higher than the 8-g/ml IC 50 determined with a plaque reduction assay endpoint (18) or the IC 50 of Ͼ500 M found in another study utilizing inhibition of CPE as an endpoint (28). RBV also failed to reach a TC 50 in most published YFV antiviral evaluation studies (20,28,29), while one study found a TC 50 for RBV of 63 g/ml (18).…”
mentioning
confidence: 99%
“…A limited number of antivirals have been tested, and few have been effective against viruses within the family Bunyaviridae. Ribavirin (1-␤-D-ribofuranosyl-1,2,4-triazole-3-carboamide) (RBV), a broad-spectrum antiviral agent, and related C-nucleoside analogues ribamidine, selenazofurin (SEL), and tiazofurin (TIA) show potent antiviral activity in vitro against HTNV (17,19). RBV was proven effective in the treatment of lethal encephalitic suckling mice infected with HTNV (16).…”
mentioning
confidence: 99%